Компетенція та повноваження керівника територіального управління Державного бюро розслідувань - Курепін, Р. Ю.; Kurepin, R. Yu. (Європейські перспективи. - 2023. - № 1. - С. 236-241, 2023)
Виокремлено ключові повноваження керівника територіального управління Державного бюро розслідувань, на основі чого відзначено, що саме вони відображають їх місце та значення у різноманітних відносинах, які виникають в діяльності підпорядкованих їм відомств, зокрема: проходження стажування, складення присяги, провадження внутрішнього контролю, тощо. Також керівники виконують роль представників тих територіальних управлінь ДБР, які вони очолюють, у відносинах з органами державної влади, органами місцевого самоврядування та громадськими об’єднаннями. Відзначено, що компетенція та повноваження керівника територіального управління ДБР є тими елементами, які разом із завданнями та функціями, розкривають зміст його адміністративно-правового статусу.

The key powers of the head of the territorial department of the State Bureau of Investigation are highlighted, based on which it is noted that they reflect their place and importance in various relationships that arise in the activities of the departments subordinate to them, in particular: internships, taking an oath, conducting internal control, etc. Managers also play the role of representatives of the territorial departments of the SBI that they lead in relations with state authorities, local self-government bodies, and public associations. It was noted that the competence and powers of the head of the territorial management of the SBI are the elements that, together with the tasks and functions, reveal the content of his administrative and legal status. Thus, the content of the manager’s competence determines the range of criminal offenses investigated by the territorial administration and the territorial coverage of his activities, as well as the powers aimed at ensuring the proper functioning of the department headed by him. In turn, the powers include the rights and obligations defined by laws and by-laws. It is argued that it is most appropriate to divide the powers of the head of the territorial board of the DBR into the following types: 1) by relation to the service: a) general, which are characteristic of him as an employee of the DBR on a par with other employees; and b) special, due to a special legal status related to the specifics of the position held; 2 by main areas of activity: intra-organizational, personnel, informationanalytical, representative, etc.

Выделены ключевые полномочия руководителя территориального управления Государственного бюро расследований, на основе чего отмечено, что именно они отражают их место и значение в разнообразных отношениях, возникающих в деятельности подчиненных им ведомств, в частности: прохождение стажировки, принесение присяги, проведение внутреннего контроля и т.д. Также руководители выполняют роль представителей тех территориальных управлений ГБР, которые они возглавляют, в отношениях с органами государственной власти, органами местного самоуправления и общественными объединениями. Отмечено, что компетенция и полномочия руководителя территориального управления ГБР являются теми элементами, которые вместе с задачами и функциями раскрывают содержание его административно-правового статуса.
Keywords: повноваження; компетенція; Державне бюро розслідувань; керівники; територіальне управління; authority; competence; State Bureau of Investigation; managers; territorial administration; полномочия; компетенция; Государственное бюро расследований; руководители; территориальное управление